2022
DOI: 10.1002/slct.202202950
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Cytotoxicity Evaluation, Docking, ADMET and Drug Likeness Studies of Secondary Metabolites from the Stem Bark ofAnthocephalus cadamba(Roxb.)

Abstract: Phytochemical investigation of the stem bark of Anthocephalus cadamba(Rubiaceae) led to the isolation of total ten secondary metabolites (1‐10) including β–sitosterol (1), ursolic acid (2), vanillic acid (3), quinovic acid (4), 3‐O‐[α‐L‐rhamnopyranosyl]‐quinovic acid (5), β‐sitosterol β‐D‐glucoside (6), cadambine (7), 3β‐dihydrocadambine (8), 7‐O‐acetyl loganin (9) and hexyl p‐coumarate (10). Four acetylated derivatives 2 a,5 a,7 aand8 aobtained through acetylation of compounds 2, 5, 7 and 8 respectively. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…8) etc. have been reported from this plant, where quinovic acid demonstrated potential anticancer property [115]. In another study, several other compounds have been reported from this plant including vincosamide-N-oxide and isodihydroamino cadambine, vincosamide, vallesiachotamine, iso-vallesiachotamine, and oleanolic acid etc., among which vallesiachotamine, iso-vallesiachotamine have shown potent anticancer activity against cancer cell line whilst all of the identified compounds did not show any toxic effect on normal cells [116].…”
Section: Anthocephalus Cadamba (Roxb) Miqmentioning
confidence: 92%
“…8) etc. have been reported from this plant, where quinovic acid demonstrated potential anticancer property [115]. In another study, several other compounds have been reported from this plant including vincosamide-N-oxide and isodihydroamino cadambine, vincosamide, vallesiachotamine, iso-vallesiachotamine, and oleanolic acid etc., among which vallesiachotamine, iso-vallesiachotamine have shown potent anticancer activity against cancer cell line whilst all of the identified compounds did not show any toxic effect on normal cells [116].…”
Section: Anthocephalus Cadamba (Roxb) Miqmentioning
confidence: 92%
“…A semi-empirical force field was utilized to predict the ligand’s binding energy concerning the specific macromolecular target. The force field predicts the binding energy of the ligand by allowing the integration of intra-molecular energies through evaluation of the energies for their bound and unbound states based on a comprehensive thermodynamic model [ 44 , 45 , 46 ]. The parameters required for docking of the ligand molecule were saved in a file named the docking parameter file [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Traditional plants considered in the current study included Allium sativum , Camellia sinusis , Zinger officinale , Nigella sativa , Punica granatum , Curcuma longa , Glycyrrhiza glabra , Taraxacum , Thymus vulgaris , Ocimum tenuiflorum , Phyllanthus emblica Linn., Trigonella foenum , Piper nigrum , etc. The above-mentioned plants have been reported for the presence of alkaloids, terpenoids, saponins, steroids, glycosides, carbohydrates, monosaccharides, and soluble starch [ 45 , 46 ]. Thus, the prepared ligand library was employed to perform virtual screening with the ARP enzyme, with the intent to identify possible leads.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations